PENGGUNAAN LITERASI DIGITAL DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KEAKTIFAN SISWA (STUDI KASUS) DI MTS NEGERI 4 BONE KECAMATAN LIBURENG KABUPATEN BONE (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine: 1) How digital literacy is applied in social studies (IPS) learning at MTs Negeri 4 Bone, Libureng District, Bone Regency. 2) The impact of using digital literacy in IPS learning on increasing student engagement at MTs Negeri 4 Bone. 3) Effective strategies for implementing digital literacy-based IPS learning models to increase student engagement. This research employs a qualitative approach using the case study method. Data collection techniques were conducted through observation, in-depth interviews with the School Principal, IPS teachers, and several students, as well as documentation. Data analysis was performed through data reduction, data presentation, and conclusion drawing. The research findings show: 1) The application of digital literacy in IPS learning is good, covering planning, implementation, and evaluation stages by utilizing digital media such as instructional videos, internet, and digital learning platforms. 2) The use of digital literacy has a significant impact on student engagement, characterized by active participation in discussions, courage in asking questions, involvement in problem-solving, and the ability to search for and process information. 3) Effective strategies are implemented through improved teacher competence, strengthened student digital literacy skills, the use of interactive learning methods, and support from school facilities and infrastructure.